Workshop Branding Sebagai Strategi Penguatan UMKM Kuliner Di Kelurahan Wonorejo Rukun Warga 08 - Zulkarnain, ACH.; Alamsyah, Bima Rafi; Amrulloh, M. Hanif; Skipper, Chiara Kathleen; Yance, Evy (Bhumiputra: Jurnal Penelitian dan Pengabdian Masyarakat Global, 2025)
This community service activity aims to improve the competitiveness of culinary MSMEs in RW 08, Wonorejo Subdistrict through a branding workshop. The workshop includes logo creation, promotional banner design, the development of a mini studio for food product photography, and the registration of MSMEs on Google Maps. A participatory approach was used with training and hands-on practice methods. The results showed an 82% increase in participants' branding knowledge and significant improvements in product appearance. This activity is expected to serve as an effective empowerment model for local MSMEs to face the digital era.